Influence of temperature, heating rate and holding time on the fixed-bed pyrolysis of rice straw - Razi, Ahmad; Khairuddin, Md Isa; Khairul Nizar, Ismail; Khudzir, Ismail; Mohd Asri, Abd Rahim (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.